L’arrivée des centres commerciaux dans les marges urbaines de Rabat : Des lieux inédits de sociabilité et de déambulation urbaine - Tarik Harroud (L’Année du Maghreb)
This article focuses on the analysis of the spatial and socio-cultural reshaping induced by the proliferation of shopping centers on the outskirts of Rabat.Commercial spaces that originated during the 90s have significantly multiplied in recent years and now constitute one of the most attractive hubs in the capital city. A look at the flows of people converging to these spaces on week-ends will attest to the importance they now hold in the social and spatial practices of a large segment of the Rabat population.With a diversified, well-staged commercial offer, these places are increasingly favored by a heterogeneous crowd, for multiple non-commercial uses reminiscent of the ambulatory habits in public streets (gathering, strolling, window-shopping, etc.) Based on a series of investigations conducted in these places (four malls in Rabat) combining solid observation of the ways and means of their social use with the analysis of representations associated with them by a sample of users, this study shows the emergence of new forms of sociability revealing a unique relationship with the city and its specific foundations (public space, urban center, urban identity, etc.). These places embody the values ​​and images of the West and consumer culture, and are a favorite spot for the young people of Rabat as ideal spaces for meeting, socializing with the opposite sex and showing off – particularly in displaying consumer goods (designer items and accessories).